Obtaining a filter material used in gas and air purification - Ergashev Y.; Egamberdiev E.; Mirkhodjaeva D.; Akmalova G.; Umarova M.; Kholdarov R. (E3S Web of Conferences, 2023)
Modern technologies allow obtaining small diameter fibers used for fine filtration. Combined layer filter materials are made from such fibers. Nanofibers from 20 to 200 nm are actively used as components of filter materials. They are made of synthetic (polyamides, polyesters, aromatic polyamides, polyacrylates), biological (proteins, collagen) materials and activated carbon. According to their effect, they are similar to reverse osmosis membranes (they retain large anions, Ca, Mg cations, heavy metal ions, large organic compounds) and at the same time allow obtaining membranes with high permeability for small sodium ions. It is known that one of the main problems of environmental protection is the reduction of atmospheric pollution. Every year, a large amount of harmful compounds - oxides, various metal compounds, as well as sulfur dioxide and nitrogen oxides, volatile organic compounds, stable organic compounds and acids are released into the atmosphere. The results of the study of the influence of the composite composition and the method of obtaining a filter material on its filtration properties and main indicators are presented.